IJCM_296A: Assessment of burden of Long Covid, and it's determinants among patients with Long Covid in the rural community in Bengaluru Rural District - A community based cross sectional study. - Gowthami P (Wolters Kluwer Medknow Publications, 2024)
Background: Longer-term consequences after SARS-CoV-2 infection are becoming an important burden to societies and healthcare systems. Long COVID-19 and post COVID-19 conditions are terms used clinically to describe ongoing or new symptoms that occur beyond 12 weeks of recovery from an acute infection, that cannot be explained by an alternative medical diagnosis. It is now understood that COVID-19 can impact on multiple organ systems, which can lead to a diverse range of persistent symptoms including fatigue, breathlessness, cough, loss of taste and/or smell, myalgia, memory issues and gastrointestinal problems. Very few studies have been conducted globally to assess the burden of Long Covid which are in hospital setting and none published in Karnataka state. This community based cross sectional study intends to bridge the gap in existing evidence pool and to influence evidence-based policy decisions at local administrative level. Objectives: To assess the prevalence of Long covid among people infected with COVID-19 in rural community Bengaluru rural district. Methodology: Community based cross sectional study was conducted between October 2023 to November 2023 in Orohalli & Jadigenahalli Panchayaths of Hoskote Taluk. After obtaining written and informed consent from the participants, all adults > 18years of age residing in identified villages, with COVID-19 RTPCR positive status, tested at least 12 weeks/ 3 months prior to the date of interviewed using a prevalidated questionare and Fatigue Assessment Scale. Data is analysed using SPSS trial version 21. Results: 420 participants were interviewed in 17 villages. Mean period between date of COVID positivity to date of interview was 490 days. 27 (6.4%) participants reported residual symptoms from COVID 19 infection suggestive of Long Covid. Majority of them complained of fatigue. Out 25 respondents with fatigue, 18 people had a score > 22 on FAS, indicative of clinical fatigue. Older age >60years, female gender, and ICU admission during infection, were associated with higher prevalence of long covid and are statistically significant (p value< 0.05) Conclusion: It is essential to determine the burden of longer-term consequences of SARS-CoV-2 infection and the needs of affected individuals, to successfully plan healthcare services and efficiently allocate public health resources.